Treatments for Decreased Sound Tolerance (Hyperacusis and Misophonia) - Jastreboff, Pawel J.; Jastreboff, Margaret M. (Seminars in Hearing, 2014)
Decreased sound tolerance (DST) is an underappreciated condition that affects the lives of a significant portion of the general population. There is lack of agreement regarding definitions, specific components, prevalence, methods of evaluation, and methods of treatment. Limited data are available on the results of treatments. Research is scant and constrained by the lack of an animal model. This article proposes a definition of DST and its division into hyperacusis and misophonia. The potential mechanisms of these phenomena are outlined, and the results of treatment performed at Emory University are presented. Out of 201 patients with DST, 165 (82%) showed significant improvement. Of 56 patients with hyperacusis (with or without misophonia), 45 (80%) showed significant improvement. This proportion was higher for the group with hyperacusis and concurrent misophonia (33 of 39, or 85%) and lower for patients with hyperacusis only (13 of 17, or 76%). Effectiveness of treatment for misophonia with or without hyperacusis was identical (152 of 184, 83% and 139 of 167, 83%, respectively, for misophonia accompanied by hyperacusis and for misophonia only). Even with current limited knowledge of DST, it is possible to propose specific mechanisms of hyperacusis and misophonia and, based on these mechanisms, to offer treatments in accordance with the neurophysiological model of tinnitus. These treatments are part of Tinnitus Retraining Therapy (TRT), which is aimed at concurrently treating tinnitus and DST and alleviating the effects of hearing loss. High effectiveness of the proposed treatments support the postulated mechanisms.
Keywords: Decreased sound tolerance; hyperacusis; misophonia; definitions; treatment